Advanced glycation end‐products suppress autophagic flux in podocytes by activating mammalian target of rapamycin and inhibiting nuclear translocation of transcription factor EB. Issue 2 (30th April 2018) - Zhao, Xingchen; Chen, Yuanhan; Tan, Xiaofan; Zhang, Li; Zhang, Hong; Li, Zhilian; Liu, Shuangxin; Li, Ruizhao; Lin, Ting; Liao, Ruyi; Zhang, Qianmei; Dong, Wei; et al.
Abstract: Insufficient autophagy in podocytes is related to podocyte injury in diabetic nephropathy (DN). Advanced glycation end‐products (AGEs) are major factors of podocyte injury in DN. However, the role and mechanism of AGEs in autophagic dysfunction remain unknown. We investigated autophagic flux in AGE‐stimulated cultured podocytes using multiple assays: western blotting, reverse transcription–quantitative PCR, immunofluorescence staining, and electron microscopy. We also utilized chloroquine and a fluorescent probe to monitor the formation and turnover of autophagosomes. Mice of the db/db strain were used to model diabetes mellitus (DM) with high levels of AGEs. To mimic DM with normal levels of AGEs as a control, we treated db/db mice with pyridoxamine to block AGE formation. AGEs impaired autophagic flux in the cultured podocytes. Compared with db/db mice with normal AGEs but high glucose levels, db/db mice with high AGEs and high glucose levels exhibited lower autophagic activity. Aberrant autophagic flux was related to hyperactive mammalian target of rapamycin (mTOR), a major suppressor of autophagy. Pharmacologic inhibition of mTOR activity restored impaired autophagy. AGEs inhibited the nuclear translocation and activity of the pro‐autophagic transcription factor EB (TFEB) and thus suppressed transcription of its several autophagic target genes. Conversely, TFEB overexpression prevented AGE‐induced autophagy insufficiency. Attenuating mTOR activity recovered TFEB nuclear translocation under AGE stimulation. Co‐immunoprecipitation assays further demonstrated the interaction between mTOR and TFEB in AGE‐stimulated podocytes and in glomeruli from db/db mice. In conclusion, AGEs play a crucial part in suppressing podocyte autophagy under DM conditions. AGEs inhibited the formation and turnover of autophagosomes in podocytes by activating mTOR and inhibiting the nuclear translocation of TFEB. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.